Determinants of Effectiveness Learning of SAP-Based Enterprise Resource Planning Courses - Marfuah; Richza Ariyo Ditama; Adinda Khansa Khairunissa (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to determine the factors that influence learning effectiveness of SAP-based Enterprise Resource Planning Courses at the Islamic University of Indonesia. Based on the theory of embodied learning, this study hypothesizes that activeness, level of suitability, perception of immersion, motivation, and technology support have a positive effect on learning effectiveness of SAP-based ERP courses. A quantitative approach with a survey method was used to collect data from 371 students in 6 study programs who had taken SAP-based ERP courses. The results of multiple regression analysis showed that physical involvement, level of suitability, motivation, and technology support had a significant positive effect on learning effectiveness of SAP-based ERP courses. However, the perception of immersion actually has a significant negative effect on the effectiveness of learning SAP-based ERP courses, which is contrary to the formulated hypothesis. These findings contribute to designing an ERP curriculum by increasing active participation, aligning materials with software features, fostering motivation, and ensuring technology infrastructure to improve learning effectiveness of SAP-based ERP courses.